Breaking Free from the Shackles: Contemporary Women's Crisis and Liberation in Her Story and Like a Rolling Stone - Wang, Xianlong; Wu, Mingzhen (Journal of Modern Social Sciences, 2025)
This paper focuses on two representative films, Her Story and Like a Rolling Stone, to explore the crisis faced by contemporary women of all ages from the perspective of feminist existentialism. It first analyzes the loss of "self" and "freedom" among contemporary women and reveals the constraints of the patriarchal society on women's self - construction. Then, it delves into the causes of women's dilemmas from the perspectives of the workplace, family, and inter - generational relationships. Finally, it analyzes the awakening and self - rescue of contemporary women. The study finds that under the long - term structural oppression of the patriarchal society, women lack subjectivity and face restrictions in self - value realization and freedom pursuit. The key for women to break free from the current predicament lies in reconstructing self - identity through self - reflection and obtaining social resources, which also requires the joint efforts of both men and women.
Keywords: Contemporary women; Existential crisis; Feminist films; Structural oppression; Self - rescue